Hands-on or no hands-on training in ultrasound imaging: a randomized trial to evaluate learning outcomes and speed of recall of topographic anatomy - Knudsen, Lars; Nawrotzki, Ralph; Ochs, Matthias (Anatomical sciences education, 2018)
Medical students have difficulties in interpreting two-dimensional (2D) topographic anatomy on sectional images. Hands-on and no hands-on training in ultrasound imaging facilitate learning topographic anatomy. Hands-on training is linked with active search for patterns of anatomical structures and might train pattern recognition for image interpretation better although the added value on learning outcomes is unclear. This study explores first year medical students’ knowledge in topographic anatomy of the upper abdomen after attending hands-on or no hands-on training in ultrasound in a randomized trial.
Gesehen am 25.11.2019